SYNTHESIS AND CHARACTERIZATION OF 2-(METHYLAMINO)ETHANOL-BASED DEEP EUTECTIC SOLVENTS FOR CO2 CAPTURE - Mohd Azlan Kassim; Ameen Gabr Ahmed Alshaghdari; Rozita Yusoff; Mohamed Kheireddine Aroua (Malaysian Journal of Science, 2024)
In recent years, deep eutectic solvents (DESs) have attracted the interest of many researchers for application in a wide range of industrial and scientific fields, including carbon dioxide (CO2) capture. DESs exhibit favourable solvent properties for CO2 removal applications; hence, they have become promising alternatives to common amine solutions and ionic liquids (ILs). In this context, a novel DES was synthesised by mixing 2 (methylamino)ethanol (2-MAE) as a hydrogen bond donor with choline hydroxide (ChOH) as a hydrogen bond acceptor with a molar ratio of ChOH:2-MAE of 1:1. The solubility of CO2 in the prepared systems was determined and characterised before and after CO2 absorption by measuring their physicochemical properties (density and viscosity) and analysing their FTIR spectra. The results showed that the DES and 2M DES aqueous solutions exhibited CO2 absorption capacities comparable to those of other reported DESs. These physicochemical properties were comparable to those reported in the literature. Besides, the FTIR analysis of the studies systems after absorption indicates the formation of carbamate.